ELECTROMYOGRAPHY INDICATORS STUDIES OF MASTICATORY MUSCLES IN PREGNANT WOMEN WITH PARTIAL DEFECTS OF DENTITION BY ROC TA AND ROC MM INDEXES - V. Pekhnyo; K. Hulavska (Ukrainian Medical Stomatological Academy, 2017)
In this article we present the results of the changes of surface potentials of the masticatory muscles in pregnant and women in postpartum period. During the execution of the study, we conducted electromyographic examination and diagnosis 58 pregnant women who applied to the Department of dentistry, Institute of dentistry, NMAPE named after P. L. Shupyk. In the course of the study was the division into two subgroups A and B (sub-group A was characterized by the presence of defects of dentition and violation of the integrity of the dentition, subgroup B - restored the integrity of the dentition through fixed prosthetic constructions). The results of electromyography average amplitude of activity of the masticatory muscles, the obtained data was entered into a formula to determine the indices of the ROC and ROC T M. Methodology of the study was conducted according to the manufacturer's recommendations (BioFLEX, USA), the obtained results were processed on a personal computer using specialized software (BioPACK BioRESEARCH Inc.,USA). The results of the research were divided on the time interval(1-trimester, 2nd trimester, 3rd trimester and postpartum), the results obtained were classified with an error of research. In group A we observed a reduction in ROC TA less than 95% from 36.7% (1st Trimester) to 35.2%(postpartum period), fluctuations in the indicator ROC TA from 95% to 105% was within 1%(7,5%-6,5%), the index of ROC TA більше105% grew from 55.8 per cent to 58.3%. Figure ROC MM less than 95% in the beginning of the study was 61.2% in all groups of patients and increased to 64,75%. Dynamics of the indicator ROC MM from 95% to 105% was 3.2% at baseline and 3.15% in the postpartum period. Fluctuations in the indicator ROC MM greater than 105% was 3.5% downward. The group was characterized by more stable indices TA ROC and ROC MM in the dynamics (in the range of 0.07% to 1.75%) compared to group 1A. The majority of surveyed indicators EMG were ROC TA from 95% to 105% and ROC MM from 95% to 105% (the difference between the first and the last visit was 0.5% and 0.66%). Change index ROC TA < 95%, TA more105 ROC% ROC MM less than 95%, ROC MM greater than 105%, respectively: 1,75%, 0,55%, 0,59% 0,07% respectively. In the study we noted the progression of changes of bioelectric activity of masticatory muscles in the indices TA ROC and ROC MM, it occurs more often in patients with defects of dentition(group a) in comparison with the control group (group B). We have obtained the dynamics of changes of bioelectric activity of masticatory muscles in pregnant and women in postpartum period and made a comparative assessment of indices in the study groups. This study indicates a significant progression of disorders of bioelectric activity of masticatory muscles in pregnant and women in postpartum period, which in turn complements the scientific view of Chumakovo Y. G. "the effects of pregnancy on the dental status of women."